A Novel Mutation in NLRP7 Related to Recurrent Hydatidiform Mole and Reproductive Failure - Fallahi, Jafar; Razban, Vahid; Momtahan, Mozhdeh; Akbarzadeh-Jahromi, Mojgan; Namavar-Jahromi, Bahia; Anvar, Zahra; Fardaei, Majid (International journal of fertility & sterility, 2019)
Hydatidiform mole (HM) is an abnormal human pregnancy with excessive trophoblastic proliferation and abnormal embryonic development, dividing into two complete HM (CHM) and partial HM (PHM) groups. One subcategory of the CHMs is recurrent and familial, which is known as biparental HM (BiHMs) or recurrent HM (RHM). , and are maternal-effect genes involved in RHMs. is a major gene responsible for RHMs. This study was performed on patients with molar pregnancies and miscarriage. The aim of this study was to genetic screen for mutations in and genes in an affected woman with previous history of 5RHM and the sibling with history of miscarriage. In this experimental study, DNA was extracted from blood samples. and were polymerase chain reaction (PCR) amplified. The PCR products were purified and Sanger sequenced. In this study, there is no mutation in gene but a novel mutation was identified in the NACHT domain of gene. Patient with five recurrent moles had this mutation in the homozygous state while her sister with one miscarriage and one normal child showed this mutation in the heterozygous state. In this study, we identified a new mutation in gene of a patient with recurrent HM. Following egg donation, this patient has a normal boy. The sister of this patient with heterozygous mutation has a spontaneous abortion and one normal child that confirm the impact of a defective allele of on reproductive wastage in a recent finding.